Degradation and Pathways of Carvone in Soil and Water - Chenyu Huang; Wenwen Zhou; Chuanfei Bian; Long Wang; Yuqi Li; Baotong Li (Molecules, 2022)
Carvone is a monoterpene compound that has been widely used as a pesticide for more than 10 years. However, little is known regarding the fate of carvone, or its degradation products, in the environment. We used GC-MS (gas chromatography–mass spectrometry) to study the fate of carvone and its degradation and photolysis products under different soil and light conditions. We identified and quantified three degradation products of carvone in soil and water samples: dihydrocarvone, dihydrocarveol, and carvone camphor. In soil, dihydrocarveol was produced at very low levels (≤0.067 mg/kg), while dihydrocarvone was produced at much higher levels (≤2.07 mg/kg). In water exposed to differing light conditions, carvone was degraded to carvone camphor. The photolysis rate of carvone camphor under a mercury lamp was faster, but its persistence was lower than under a xenon lamp. The results of this study provide fundamental data to better understand the fate and degradation of carvone and its metabolites in the environment.